Egyetemi legendárium – emlékek, töredékek a debreceni tudományegyetem történetéből III. rész - Vincze, László (Gerundium, 2016)
Memoirs of László Vince, Part iii. László Vince was first employed by the University of Debrecen in 1951, as a stenographer at the University Study Notes Office. When this office was dismantled, from 1952 he worked at the Registrar’s Office of the School of Arts. In 1956 he was transferred to the Rector’s Office, where, in 1972, he was promoted to head the department of international programs. This position, which he held until his retirement in 1990, was actually equivalent to the rank of rector’s secretary. During hisyears of employment he acquired an enormous amount of experience, which was partly due to the fact that in the 1950s he could still talk to the representatives of the previous political order. His detailed but strongly subjective reminiscences – supplemented with necessary footnoting pertaining to the sources used – is published here as the third part of three interrelated texts.